Melody and Morphology: The Role of Songs in Teaching Verbal Structures of Foreign Languages - Amos, Nsikak Bernard (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
Verbs are important component of syntax and play a crucial role on how learners express meaning, both orally and in writing. This study explores how Daouda’s song La femme de mon patron can be used as a practical tool for teaching French verbal structures to foreign language learners. The song was chosen because it contains a wide range of verbs, presented in clear and standard French, free from slang or dialectal forms that might confuse beginners. Through its simple yet culturally engaging lyrics, the song provides repeated exposure to verbs in declarative, conditional, and interrogative forms. The study demonstrates how teachers can use songs to enhance oral and written competence. Orally, students practice pronunciation, rhythm, and prosody in a natural context. In writing, the song enables activities such as verb identification, conjugation drills, and sentence transformation. The findings show that learners improved in verb identification with 80% accuracy and exhibited greater confidence in oral and written tasks. The study underscores the potential of integrating songs as structured grammar tools rather than supplementary activities. This study demonstrates that when carefully selected, songs can serve as instructional support for teaching verbs in foreign language classrooms compared to traditional grammar instruction. It concludes by proposing methodological guidelines for integrating songs into the teaching of verbal structures in French.